Argumentação na formação do professor na escola bilíngue - Meaney, Maria Cristina (2009)
The objective of the research is to critically understand how the actions of partnered teachers, especially their e-mail exchanges, which aim at developing the curriculum as well as the didactic sequences developed in English at a bilingual school in São Paulo, promote the creation of a context of collaboration in which is possible to expose and confront their senses related to teaching the subject of science. As part of the project Arguments in the creative production of meaning in school contexts of educators formation (LIBERALI, 2008), this research was done under the possibility that argumentation be an instrument that allows interlocutors to expose their senses in search of a consensus understood here as meaning construction enabling participants personal and professional development. The concepts of sense and meaning (VYGOTSKY, 1934/2005) and zone of proximal development (VYGOTSKY 1934/2005; NEWMAN e HOLZMAN, 2002) give theoretical support to this work, as well as the Social Historical and Cultural Activity Theory (LEONTIEV, 1977; ENGESTRÖM, 1999). The data analyses focuses on the argumentative potential of the interactions and is based on the categories proposed by Perelman e Olbrechts-Tyteca(2005) and Reboul (2004) based on Aristotle. It is a critical collaboration research (MAGALHÃES, 2002, 2004 e 2007), as it aims at the transformation of the participants and has language as its central issue. The analysis shows that, when trying to untie the knots that appear in the interaction, the teachers intensify their argumentation in an attempt to clarify their senses, transforming the exchange of e-mails in a context of collaboration among them. In this process, new meanings about teaching science in a bilingual school are constructed